2010
DOI: 10.1373/clinchem.2009.134858
|View full text |Cite
|
Sign up to set email alerts
|

Full-Length Characterization of Proteins in Human Populations

Abstract: BACKGROUND: Diversity in human proteins often gives rise to pluralities of structurally similar but functionally distinct proteins. Such microheterogeneity generally escapes proteomics discovery technologies, as well as conventional immunometric assays. As an intermediate between these 2 technological approaches, targeted, full-length characterization of proteins using mass spectrometry is a suitable means of defining microheterogeneity evident in human populations. CONTENT:We describe and explore the implicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 35 publications
(41 reference statements)
0
34
0
Order By: Relevance
“…In contrast, we found that DBP level was increased in diabetic rat serum. One explanation for the discrepancy is the specificity of DBP antibodies (Borges et al, 2010). In other words, microheterogeneity (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we found that DBP level was increased in diabetic rat serum. One explanation for the discrepancy is the specificity of DBP antibodies (Borges et al, 2010). In other words, microheterogeneity (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation could be potentially different isoforms of the apolipoproteins, with differences in which isoforms can be detected by the method employed. A recent paper by Borges et al [34] reviews the microheterogenity of the human proteome. Evidently, polymorphisms, transcript variants and posttranslational modifications give rise to structurally similar but functionally distinct proteins whose detection is platform-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…GC 2 has the Sty I but not the Hae III site. The existence of both restriction sites on a single haplotype has not yet been characterized [26]. …”
Section: Methodsmentioning
confidence: 99%